1995
DOI: 10.1073/pnas.92.20.9402
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the overtone of the Fe-CO stretching mode in heme proteins: a probe of the heme active site.

Abstract: Two CO-isotope sensitive lines have been detected in the overtone region of the resonance Raman spectra of CO-bound hemeproteins. One line is assigned as the overtone of the Fe-CO stretching mode and is located in the 1000-to 1070-cm'1 region. The other line is found in the 1180-to 1210-cmn-' region and is assigned as a combination between a porphyrin mode, V7, and the F6-CO stretching mode. The high intensities of these lines, which in the terminal oxidase class of proteins are of the same order as those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…The modes at 1464 and 1490 cm Ϫ1 originate from the ferrous, five-coordinate high spin heme a 3 2ϩ and the ferrous six-coordinate low-spin heme a, respectively. The mode at 1519 originates from 19 of heme a 2ϩ . The modes at 1569 and 1584 cm Ϫ1 originate from 2 of heme a 3 2ϩ and heme a, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The modes at 1464 and 1490 cm Ϫ1 originate from the ferrous, five-coordinate high spin heme a 3 2ϩ and the ferrous six-coordinate low-spin heme a, respectively. The mode at 1519 originates from 19 of heme a 2ϩ . The modes at 1569 and 1584 cm Ϫ1 originate from 2 of heme a 3 2ϩ and heme a, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Non-FC dependence of the electronic transition moment on the vibrational coordinate is possible through B-term and C-term enhancement. [6] When the excitation is in resonance with the weaker Q 0 band at approximately 575 nm, B-term scattering dominates,[7] which involves vibronic coupling between two allowed excited electronic transitions. Early studies on metalloporphyrins in solution showed that both Q 0 and Q v bands are predominantly governed by the strong Herzberg–Teller coupling of antisymmetric A 2g modes,[8, 9] providing evidence of vibronic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[7, 17] Strekas and Spiro reported that, although RR spectra sometimes display intense overtone progressions, these are not apparent in the RR spectra of Hb. [20] It is important to note that these early reports were based on what was known from solution-phase studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations